Oral Hematomas following Oral Sex in Individuals with Disrupted Coagulation - Tobias, G; Chackartchi, T; Abramov, L; Mann, J; Findler, M (Archives of Clinical and Medical Case Reports, 2022)
Protected oral sex is relatively safe and harmless. There are hardly any reports in the literature regarding palatal bruises and hematomas following oral sexual activity in those with a bleeding tendency. Here we report oral sub-mucosal hemorrhage in three women with a disrupted coagulation system. The traumatic hemorrhage was attributed to violent activity during oral sexual practices. This short report presents a seemingly unnoticed and unreported phenomenon following oral sexual behavior.